Dysphagia and aspiration during a Parkinson's hospitalization: a care partner's perspective and recommendations for improving standards of care - Brooks, Annie (Frontiers in Aging Neuroscience, 2023)
People with Parkinson's have significantly increased incidence and risk of aspiration pneumonia when compared to those without aspiration pneumonia associated with dysphagia (issues with swallowing) is the leading cause of death among people with Parkinson's, accounting for 25% of Parkinson's deaths. When a person with Parkinson's develops aspiration pneumonia in the hospital and dies while hospitalized or shortly after discharge, care partners are often left wondering if a different outcome may have been possible if their clinicians had a better understanding of Parkinson's or if accepted standards of care had been in place.There is relatively limited evidence of the most effective strategies to balance competing needs of each Parkinson's patient as providers aim to prevent, diagnosis, and manage dysphagia. Exacerbated, and in part caused, by the intricacies of dysphagia and Parkinson's, there is still limited understanding amongst hospital providers and the Parkinson's community regarding the most appropriate measures to prevent and manage dysphagia in Parkinson's. The Parkinson's Foundation Hospital Care Recommendations identified the prevention and management of dysphagia as a care standard necessary to eliminate harm and attain higher reliability in care.